Transformation of Contemporary Cost Management Paradigms: A Systematic Literature Review from Strategic and Value-Based Perspectives - Shera Nabila Luvianingtias; Rahayu Lestari; Nur Fahmuddin Hanif; Heni Noviarita; Romlah Romlah (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines the transformation of contemporary cost management paradigms within the context of an increasingly dynamic and digitalized business environment, where cost management is no longer limited to operational control but evolves into a strategic tool for value creation and sustainable competitive advantage. The purpose of this research is to analyze how cost management has shifted toward strategic and value-based approaches and to integrate various contemporary perspectives into a comprehensive conceptual framework. This study employs a qualitative approach using a Systematic Literature Review (SLR) method by analyzing peer-reviewed articles published between 2021 and 2026 from reputable databases, following PRISMA guidelines to ensure validity and transparency. The findings indicate a significant transition from traditional costing to strategic cost management, supported by digital transformation that enhances real-time data processing, accuracy, and decision-making quality. Additionally, the evolution of Activity-Based Costing (ABC) and the adoption of value-based cost management approaches contribute to improved efficiency, identification of value-added activities, and strengthened organizational performance. In conclusion, contemporary cost management has become a strategic, technology-driven, and value-oriented system that plays a crucial role in enhancing competitiveness and ensuring long-term organizational sustainability.